Effectiveness of otago exercise programme on physical performance, functional capacity and self-confidence on falls among elderly people in Shahroud, Iran - Dadgari, Ali (2014)
Falls in older people are very common and its incidence increases with age. In the community, the proportion of people who sustain at least one fall varies from 28% to 35% annually among those aged 65 years. The purpose of this study was to examine the effects of a home based-exercise training programme on physical performance, functional capacity and incidence of falls among elderly community dwellers and to test the mediation effect of self-efficacy on the relationship between physical performance and functional capacity and fall. Bandura’s self-efficacy theory and the Transtheoretical Model (TTM) of exercise behaviour were theoretical framework of the study. Based on self-efficacy theory, exercise improves physical performance and functional capacity. In addition,transtheoretical model of exercise behaviour explained subjects’ changing behaviour and staying on attained behaviour for at least 6 consecutive months. This is a randomized control trial, with 317 subjects in control (n=157) and experimental (n=160) groups. Statistical analyses such as frequency, mean, standards deviation, t-Test and other compare means analyses were conducted. In addition, this study explored the best model fit for fall reduction due to exercise training. According the findings of this study, six months home-based Otago exercise training programme improves physical performance and functional capacity, which in turn can reduce the incidence of fall and repeated falls. Participants in experimental group,showed significant decline in frequency of falls (p value> .00). Other finding of this study indicated that the relationship between physical performance and functional capacity with declined falls incidence is mostly due to self-efficacy gained through exercise training (CFI=1, RMSEA= .00). In other words, the findings of this study showed that self-efficacy can play a role between the relationships of physical functioning and falls reduction among elderly people. This study highlighted the role of self-efficacy as a mediator between the relationship of physical functioning and fall reduction among elderly people.